2001
DOI: 10.1007/s004410100442
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diethylstilbestrol on the cytogenesis of prolactin cells in the pars distalis of the pituitary gland of the mouse

Abstract: This study was carried out to examine the developmental stage when prolactin cells differentiate in mice and to examine the effects of diethylstilbestrol on the development of prolactin cells in the fetal and neonatal pituitary glands. A small number of immunoreactive prolactin cells appeared first on embryonic day 15 in control (injected with oil) pituitary glands, whereas they did not increase in number until postnatal day 2. In diethylstilbestrol-treated mice (5 mg/kg body weight, 24 h before killing), a sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 37 publications
4
19
0
Order By: Relevance
“…In the pituitary, it is known that treatment with DES causes pituitary hyperplasia followed by the development of prolactinomas (Walker and Kurth 1993), and DES increased the prolactin (PRL) cell population in rodent pituitaries (Cauwenberge et al 2001;Matsubara et al 2001). However, the precise mechanism of DES effect on pituitary cells remains unclear.…”
Section: Introductionmentioning
confidence: 98%
“…In the pituitary, it is known that treatment with DES causes pituitary hyperplasia followed by the development of prolactinomas (Walker and Kurth 1993), and DES increased the prolactin (PRL) cell population in rodent pituitaries (Cauwenberge et al 2001;Matsubara et al 2001). However, the precise mechanism of DES effect on pituitary cells remains unclear.…”
Section: Introductionmentioning
confidence: 98%
“…These cells are considered to arise from a common precursor cell, and the sequential expression of transcription factors involved in pituitary organogenesis induces differentiation into different endocrine cells. Pituitary endocrine cell development and the specific production of these transcription factors may be controlled by some extracellular signaling molecules, such as fibroblast growth factor 8, bone morphogenetic protein 4 and Wnt5a (Treier et al 1988, Sheng & Westphal 1999, Dasen & Rosenfeld 2001, and steroid hormones (Nogami et al 1995, Stahl et al 1999, Matsubara et al 2001. In addition, the potent ability of cytokines such as leukemia inhibitory factor (Akita et al 1997) might be considered to be essential for pituitary development.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that long-term E 2 treatment induces mammotrophic pituitary tumors [22,23]. Moreover, diethylstilbestrol could induce PRL cell differentiation in the fetal mouse pituitary [24], and promote PRL cell proliferation in the adult pituitary [25,26]. In this study, we assessed the effect of co-treatment with E 2 and corticosterone on MtT/SM cells, and found that co-treatment with E 2 and corticosterone (10 -12 -10 -9 M) had an additive effect on the induction of PRL-immunopositive cells.…”
Section: Discussionmentioning
confidence: 99%